Stem Cells and the Regeneration of the Aging Cardiovascular System - Ballard, Victoria L.T.; Edelberg, Jay M. (Circulation research, 2007)
It is well established that cardiovascular repair mechanisms become progressively impaired with age and that advanced age is itself a significant risk factor for cardiovascular disease. Although therapeutic developments have improved the prognosis for those with cardiovascular disease, mortality rates have nevertheless remained virtually unchanged in the last twenty years. Clearly, there is a need for alternative strategies for the treatment of cardiovascular disease. In recent years, the idea that the heart is capable of regeneration has raised the possibility that cell-based therapies may provide such an alternative to conventional treatments. Cells that have the potential to generate cardiomyocytes and vascular cells have been identified in both the adult heart and peripheral tissues, and in vivo experiments suggest that these cardiovascular stem cells and cardiovascular progenitor cells, including endothelial progenitor cells, are capable of replacing damaged myocardium and vascular tissues. Despite these findings, the endogenous actions of cardiovascular stem cells and cardiovascular progenitor cells appear to be insufficient to protect against cardiovascular disease in older individuals. Because recent evidence suggests that cardiovascular stem cells and cardiovascular progenitor cells are subject to age-associated changes that impair their function, these changes may contribute to the dysregulation of endogenous cardiovascular repair mechanisms in the aging heart and vasculature. Here we present the evidence for the impact of aging on cardiovascular stem cell/cardiovascular progenitor cell function and its potential importance in the increased severity of cardiovascular pathophysiology observed in the geriatric population.